Experimental investigation of photovoltaic-thermoelectric hybrid systems enhanced by a heatsink and radiation reflector - Pawatwong Bamroongkhan; Mati Nararom (International Journal of Renewable Energy Development, 2026)
This study presents the design and performance evaluation of a hybrid photovoltaic-thermoelectric (PV–TEG) power generation system enhanced by the integration of a heat sink and a radiation reflector under various thermal-management conditions. The primary objective was to investigate the combined effect of these two methods on power output and system efficiency without expanding the PV installation area. The experimental setup encompassed five configurations (A–E), including natural convection, integration of thermoelectric modules, addition of reflective panels, and active cooling using air suction or forced air ventilation. Results demonstrate that all PV–TEG configurations yielded higher power outputs and greater efficiencies than the standalone PV system. Notably, configuration E, which combined radiation reflection with forced-air cooling, achieved the highest performance, increasing the electrical output by approximately 1.27 watts and reaching a peak efficiency of approximately 28.6%. The integration of TEG modules contributed an additional maximum of 2.2% to the total energy output by harvesting the excess thermal energy. Further analysis revealed significant correlations between solar irradiance, temperature, and electrical efficiency. These results highlight the potential of PV–TEG hybrid systems to effectively harness both solar and thermal energy, particularly in high-temperature and high-irradiance environments.